Groundwater Aquifer Vulnerability Assessment using a Dar-Zarrouk Parameter in a Proposed Aboru Residential Estate, Lagos State, Nigeria - M.A. Ayuk (Journal of Applied Sciences and Environmental Management)
The need to build an automobile mechanic settlement, abattoir and a proposed meat processing factory at Aboru residential estate necessitated a geophysical assessment (using a Dar-Zarrouk parameter – longitudinal unit conductance, S) of the vulnerability of the subsurface aquifers in the study area against the expected long-term anthropogenic impacts of these facilities on the groundwater system. Thirteen (13) Vertical Electrical Sounding (VES) points and four (4) Dipole-Dipole resistivity profile lines were occupied on four traverse lines across the study area. Isoresistivity and Isopach maps were generated and Total Longitudinal Unit  Conductance, S of the earth materials overlying the aquifer was computed and the aquifer protective capacity (APC) map was generated. The VES delineated four (4) geo-electric layers namely; topsoil, pebbly/lateritic sand, clay/clayey/silty sand and sandstone. The depth to the sandstone aquifer ranges from 30.6 – 39.4 m with resistivity values ranging from 851 – 1437 Ωm. The iso-resistivity and isopach maps reveal that the near surface lateritic materials with resistivity values ranging from 350 – 1150 Ωm and thicknesses ranging from 2 – 29 m are pervious. The Total Longitudinal Unit Conductance, S varies from 0.0164 - 0.1168 mhos indicating a poor to weak protective capacity rating across the study area and the APC map reveals that the north-eastern and western parts of the study area show areas with weak protective capacity ratings while other areas are characterized by poor protective capacity rating. As such, the establishment of the proposed service facilities in the study area is strongly discouraged as the nature of their operations has a high potential to contaminate and eventually pollute the sub-surface aquifers on the long-run. If however the inevitability of their establishment cannot be set-aside, then secondary measures must be taken to forestall a direct impact of their operations on the subsurface.